Encircling Ethnomethodology. Karin Knorr-Cetina in Conversation with Hannes Krämer & René Salomon - Knorr Cetina, Karin; Krämer, Hannes; Salomon, René (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In the following interview, Karin Knorr-Cetina speaks about her experience of and engagement with the book "Studies in Ethnomethodology" (GARFINKEL 1967), and about the book's intellectual environment in the U.S. and in Germany. In doing so, she differentiates an orthodox versus an open understanding of ethnomethodology. Even though the latter may not always be labeled ethnomethodology, it is strongly influenced by this perspective because it focuses on the accomplishments of everyday processes by its competent members. At the same time, she sketches the methodological implications of ethnomethodology for qualitative research in general and ethnography in particular. In this context, KNORR-CETINA identifies original principles of ethnomethodology such as everyday-ness, slowness, and anti-interpretativity, which still make ethnomethodology a relevant research perspective today. Finally, she positions ethnomethodology within current debates in social theory, for example, in relation to practice theory.